New Trends in Medical and Service Robotics Advances in Theory and Practice - Carbone, Giuseppe; Ceccarelli, Marco; Pisla, Doina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book contains the selected papers of the Sixth International Workshop on Medical and Service Robots (MESROB 2018), held in Cassino, Italy, in 2018. The main topics of the workshop include: design of medical devices, kinematics and dynamics for medical robotics, exoskeletons and prostheses, anthropomorphic hands, therapeutic robots and rehabilitation, cognitive robots, humanoid and service robots, assistive robots and elderly assistance, surgical robots, human-robot interfaces, haptic devices, and medical treatments.
Papers on topics including (but not limited to): Design of medical devices -- Kinematics and Dynamics for medical robotics -- Exoskeletons and prostheses -- Anthropomorphic hands -- Therapeutic robots and rehabilitation -- Cognitive robots -- Humanoid & Service robots -- Assistive robots and elderly assistance -- Surgical robots -- Human-robot interfaces -- Haptic devices -- Medical treatments.
Keywords: Control engineering; Robotics; Automation; Biomedical engineering; Biotechnology; Biomechanics; Control, Robotics, Automation; Biomedical Engineering and Bioengineering; Biotechnology; Biomechanics